A high-strength magnesium-based composite material and a method for preparing the same

CN122879574APending Publication Date: 2026-10-09INSTITUTE OF MATERIALS & INTELLIGENT MANUFACTURING JIANGXI ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611353349.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0007]针对上述现有技术的不足,本发明提供一种高强度镁基复合材料及其制备方法,通过引入Ti+TC4+SiC三元多尺度复合增强体系,搭配双级均匀化固溶处理、二段梯度挤压、低温多段轧制、时效热处理的制备工艺,解决单一增强相强化效率低、增强相分散不均、界面结合强度不足的行业共性难题,实现镁基复合材料抗拉强度突破550MPa的目标

Benefits of technology

(1)本发明不再使用单一增强相,而是引入Ti、TC4、SiC三种不同尺度、不同性质的增强颗粒。Ti颗粒为高纯度金属相,塑性好;TC4颗粒为高强度Ti合金相;SiC颗粒为亚微米至微米级陶瓷相,硬度高。三种颗粒通过不同尺度的级配搭配,实现了亚微米到微米尺度的多尺度协同强化,产生了明显的协同强化效应,使复合材料抗拉强度突破550MPa,达到高强铝合金的强度水平,同时保留了镁合金低密度的优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879574A_ABST
    Figure CN122879574A_ABST
Patent Text Reader

Abstract

The application provides a high-strength magnesium-based composite material and a preparation method thereof, and belongs to the technical field of metal-based composite materials. The composite material is composed of a magnesium matrix and a multi-scale composite reinforcing phase uniformly dispersed in the magnesium matrix. The magnesium matrix is a Mg-Gd-Y-Zn-Mn magnesium alloy, which contains Gd 12.6%, Y 1.3%, Zn 0.9%, Mn 0.5%, and the balance of Mg and inevitable impurities. The multi-scale composite reinforcing phase is composed of Ti particles, TC4 particles and SiC particles, and the mass fractions of the three are Ti≤4%, TC4≤7% and SiC≤2% respectively, and the particle sizes are 0.1-25 μm, 15-53 μm and 0.1-5 μm respectively. The preparation method comprises the following steps: melting and casting, two-stage homogenization and solid solution, two-stage gradient extrusion, low-temperature multi-stage rolling and aging heat treatment. The tensile strength of the obtained composite material reaches 550-600 MPa, the yield strength reaches 480-520 MPa, and the elongation rate is maintained at 2.0-3.0%, and the composite material can be used in the fields of aerospace and high-end automobiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal matrix composites, specifically a high-strength magnesium matrix composite material and its preparation method. Background Technology

[0002] The Mg-Gd-Y-Zn-Mn series of rare-earth magnesium alloys, utilizing the synergistic strengthening effect of long-period stacked ordered phases and age-precipitated phases, represents a key research direction in the field of high-strength magnesium alloys. Researchers both domestically and internationally are continuously optimizing the processes for this alloy system, hoping to further improve its mechanical properties and meet the increasing demands for lightweight structural materials in aerospace, high-end transportation, and other fields.

[0003] Regarding the optimization of alloy composition and processing, existing technologies can achieve a tensile strength of 521 MPa by adding multi-stage aging treatment before deformation of Mg-Gd-Y-Zn-Mn alloys; and by using differential temperature extrusion to process these alloys, the tensile strength can reach 496 MPa. These results indicate that relying solely on adjusting alloy composition and optimizing processing techniques, the potential for strength improvement in Mg-Gd-Y-Zn-Mn alloys is limited, making further breakthroughs difficult.

[0004] To overcome this bottleneck, researchers began experimenting with adding reinforcing phases to magnesium alloys. These phases, with their high strength and high modulus, help bear some of the load, thus achieving higher strength. The conventional approach is to add Ti or SiC particles alone as reinforcing phases, which can increase the strength of magnesium alloys by approximately 20%.

[0005] However, the practice of adding a single reinforcing phase has encountered three common problems in practical applications, making it difficult for this technical route to overcome the strength threshold of 550 MPa: (1) When Ti particles or SiC particles are added alone, the strength of the magnesium matrix can only be slightly improved due to the single strengthening method. When the amount added is small, the strengthening effect is not obvious; when the amount added is too large, the reinforcing phase itself is prone to agglomeration and damages the matrix, resulting in a decrease in strength. (2) The wettability of Ti particles and SiC particles with magnesium melt is not ideal. In addition, the density between the particles and the matrix is ​​different. If conventional casting methods are used, the reinforcing phase is prone to agglomeration. Agglomerated reinforcing phases not only fail to play a strengthening role, but also cause local stress concentration inside the material. These parts are prone to become the starting point of crack initiation, which greatly reduces the plasticity and service stability of the composite material. (3) The reinforcing phase and the magnesium matrix have large differences in physical properties such as thermal expansion coefficient and elastic modulus. Without interface treatment, it is difficult for the two to form an effective metallurgical bond. Weak interfacial bonding makes it difficult to effectively transfer loads from the matrix to the reinforcing phase, thus rendering the reinforcing phase ineffective in bearing loads. At the same time, debonding defects are prone to form at the interface during deformation, which also cannot effectively prevent crack propagation, making it very difficult to improve the material's strength and toughness in a coordinated manner.

[0006] The three problems mentioned above are not isolated. Since the strengthening effect of a single reinforcing phase is limited, achieving higher strength requires increasing the amount of reinforcing phase added. However, a larger amount further worsens the dispersion uniformity of the reinforcing phase and exacerbates interfacial bonding issues, ultimately making it difficult for a single-reinforcing-phase system to break through the 550 MPa strength limit. Therefore, to significantly improve the strength of magnesium-based composites, it is necessary to simultaneously improve the strengthening efficiency of the reinforcing phase itself, the dispersion uniformity of the reinforcing phase in the matrix, and the interfacial bonding state between the reinforcing phase and the matrix—all of which are difficult to achieve in a single-reinforcing-phase system. Summary of the Invention

[0007] To address the shortcomings of the existing technologies, this invention provides a high-strength magnesium-based composite material and its preparation method. By introducing a Ti+TC4+SiC ternary multi-scale composite reinforcement system, combined with a preparation process of two-stage homogenization solution treatment, two-stage gradient extrusion, low-temperature multi-stage rolling, and aging heat treatment, the invention solves the common industry problems of low strengthening efficiency of single reinforcing phase, uneven dispersion of reinforcing phase, and insufficient interfacial bonding strength, thereby achieving the goal of breaking through 550MPa in the tensile strength of magnesium-based composite materials.

[0008] To achieve the above objectives, the present invention provides the following solution: In a first aspect, the present invention provides a high-strength magnesium-based composite material, characterized in that it is composed of a magnesium matrix and a multi-scale composite reinforcing phase uniformly dispersed within the magnesium matrix; The magnesium matrix is ​​a Mg-Gd-Y-Zn-Mn series magnesium alloy, which contains the following components by mass percentage: Gd 12.6%, Y 1.3%, Zn 0.9%, Mn 0.5%, with the balance being Mg and unavoidable impurities; The multi-scale composite reinforcing phase is composed of Ti particles, TC4 particles, and SiC particles. Based on the total mass of the magnesium matrix composite, the mass fractions of Ti particles, TC4 particles, and SiC particles are Ti≤4%, TC4≤7%, and SiC≤2%, respectively. Furthermore, the Ti particles, TC4 particles, and SiC particles exhibit a multi-scale gradation distribution in the magnesium matrix, wherein the particle size of Ti particles is 0.1-25 μm, the particle size of TC4 particles is 15-53 μm, and the particle size of SiC particles is 0.1-5 μm.

[0009] Furthermore, the purity of Ti particles is ≥99.99%, and the purity of TC4 particles and SiC particles is ≥90%.

[0010] Furthermore, based on the total mass of the magnesium-based composite material, the mass fractions of Ti particles, TC4 particles, and SiC particles were 1.2%, 4%, and 0.9%, respectively.

[0011] Furthermore, the obtained magnesium-based composite material has a room temperature tensile strength of 550-600 MPa, a yield strength of 480-520 MPa, and an elongation of 2.0-3.0%.

[0012] Secondly, the present invention provides a method for preparing the above-mentioned high-strength magnesium-based composite material, comprising: S1. Melting and casting: Weigh Mg, Gd, Y, Zn and Mn raw materials according to the proportion, melt and refine them in vacuum, add the corresponding amount of Ti particles, TC4 particles and SiC particles based on the total mass of the target magnesium-based composite material, mix them evenly and cast them into a composite ingot. S2, Two-stage homogenization solution treatment: The composite ingot is kept at 400-450℃ for 4 hours, then at 500℃ for 12 hours, air-cooled for 5-15 minutes, and then water-quenched to room temperature to obtain a solution-treated billet. S3. Two-stage gradient extrusion: The solution-treated billet is subjected to a first stage extrusion and a second stage extrusion in sequence. The first stage extrusion temperature is 470-530℃, the extrusion ratio is 9, and the speed is ≤3mm / s; the second stage extrusion temperature is 370-430℃, the extrusion ratio is 7, and the speed is ≤3mm / s, to obtain an extruded profile. S4. Low-temperature multi-stage rolling: The extruded profile is rolled in multiple passes at 150-250℃, with a reduction of 1-2% per pass and a total reduction of ≤10%, to obtain the rolled material. S5. Aging heat treatment: The rolled material is held at 150-250℃ for 3-4 hours and then air-cooled to obtain the high-strength magnesium-based composite material.

[0013] Furthermore, in step S2, the air cooling time is 10 minutes.

[0014] Furthermore, in step S3, the first extrusion temperature is 500℃ and the speed is 3mm / s, and the second extrusion temperature is 400℃ and the speed is 0.1mm / s.

[0015] Furthermore, in step S4, the rolling temperature is 200°C, the total reduction is 6%, and the reduction per pass is 1%.

[0016] Furthermore, in step S5, the aging temperature is 200℃ and the holding time is 3h.

[0017] Furthermore, in step S1, the added Ti particles have a particle size of 0.1-25 μm and a purity of ≥99.99%; TC4 particles have a diameter of 15-53 μm and a purity of ≥90%; The SiC particles have a particle size of 0.1-5μm and a purity of ≥90%.

[0018] Beneficial effects Compared with the prior art, the present invention has the following significant advantages: (1) This invention no longer uses a single reinforcing phase, but introduces three reinforcing particles of different sizes and properties: Ti, TC4, and SiC. Ti particles are a high-purity metallic phase with good plasticity; TC4 particles are a high-strength Ti alloy phase; and SiC particles are a submicron to micron-scale ceramic phase with high hardness. Through the gradation and matching of the three particles at different sizes, multi-scale synergistic strengthening from the submicron to the micron scale is achieved, resulting in a significant synergistic strengthening effect. This enables the tensile strength of the composite material to exceed 550 MPa, reaching the strength level of high-strength aluminum alloys, while retaining the low density advantage of magnesium alloys.

[0019] (2) This invention utilizes a multi-stage deformation process combining two-stage gradient extrusion with low-temperature multi-stage rolling to ensure that the reinforcing phase is fully dispersed in the magnesium matrix under intense triaxial compressive stress, effectively eliminating the agglomeration of the reinforcing phase. Simultaneously, the large deformation introduces a higher density of crystal defects such as dislocations, improving the interfacial bonding between the reinforcing phase and the matrix, forming a good metallurgical bonding interface, and effectively solving the problem of interfacial debonding in traditional composite methods. During the deformation process, the matrix grains undergo dynamic recrystallization, obtaining a fine-grained structure, further improving the comprehensive mechanical properties of the material.

[0020] (3) The present invention adopts a two-stage solid solution method of first holding at 400-450℃ for 4 hours and then holding at 500℃ for 12 hours, which effectively eliminates the component segregation and coarse second phase generated during the casting process, and avoids abnormal grain growth that may be caused by long-term high-temperature holding, thus providing a billet with uniform composition and fine structure for subsequent plastic deformation.

[0021] (4) The aging heat treatment causes a large amount of nanoscale reinforcing phase to precipitate in the matrix, which forms a superposition effect with the multi-scale reinforcing phase, thereby further improving the strength of the material. Laboratory verification shows that the composite material prepared by this invention has a stable tensile strength of 550-600 MPa, a yield strength of 480-520 MPa, and an elongation of 2.0-3.0%, achieving a good match between strength and plasticity. Attached Figure Description

[0022] Figure 1 The tensile curves of the magnesium-based composite material corresponding to Example 1 are shown.

[0023] Figure 2 The tensile curves of the magnesium-based composite material corresponding to Comparative Example 1 are shown.

[0024] Figure 3 The tensile curves of the magnesium-based composite material corresponding to Comparative Example 2 are shown.

[0025] Figure 4 The tensile curves of the magnesium-based composite material corresponding to Comparative Example 3 are shown.

[0026] Figure 5 The tensile curves of the magnesium-based composite material corresponding to Comparative Example 4 are shown. Detailed Implementation

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below. The following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Experimental methods not specifying specific conditions in the embodiments are generally performed under conventional conditions in the art or under conditions recommended by the manufacturer.

[0028] The high-strength magnesium-based composite material provided by this invention lies in the synergistic control of the entire process of material composition and preparation technology. The material composition and preparation method are described in detail below.

[0029] This invention uses a high rare earth Mg-Gd-Y-Zn-Mn series magnesium alloy as the matrix, which contains, by mass percentage: Gd 12.6%, Y 1.3%, Zn 0.9%, Mn 0.5%, with the balance being Mg and unavoidable impurities.

[0030] The specific functions of each component are as follows: With a Gd content of 12.6%, Gd is the most abundant rare earth element in this invention. Gd exhibits high solid solubility in the magnesium matrix, allowing it to dissolve extensively during solidification and subsequent heat treatment, resulting in significant solid solution strengthening. Furthermore, Gd is a key element in the formation of long-period stacked ordered phases. In synergy with Zn, it promotes the formation of these phases, which possess high hardness and thermal stability, effectively hindering dislocation movement and crack propagation. This makes Gd one of the core strengthening phases for achieving ultra-high strength in materials.

[0031] With a Y content of 1.3%, it also exhibits strong solid solution strengthening effects, and its synergistic effect with Gd promotes the precipitation of more fine and dispersed age-aged phases. The atomic radius of Y differs significantly from that of Mg, resulting in greater lattice distortion and enhancing the solid solution strengthening effect. Furthermore, Y can improve the heat resistance of magnesium alloys and inhibit grain growth during high-temperature deformation.

[0032] With a zinc content of 0.9%, Zn is an essential element for the formation of long-period stacked ordered phases. In Mg-Gd-Y alloys, Zn works together with Gd and Y to form long-period stacked ordered phases with layered structures at grain boundaries and within grains, effectively strengthening the matrix. Simultaneously, Zn improves the alloy's casting and plastic processing properties.

[0033] With a Mn content of 0.5%, Mn primarily functions to refine the grains in magnesium alloys, inhibiting grain growth during heating and providing a fine initial grain structure for subsequent plastic deformation. Furthermore, Mn can form high-melting-point compounds with Fe impurities in the alloy, reducing the adverse effects of impurities on alloy properties and improving the alloy's corrosion resistance.

[0034] This invention uses Ti particles, TC4 particles, and SiC particles to form a multi-scale composite reinforcing phase system. Based on the total mass of the magnesium-based composite material, the mass fractions of the three particles are Ti ≤ 4%, TC4 ≤ 7%, and SiC ≤ 2%. The particle size ranges for the three particles are: Ti particles 0.1-25 μm, TC4 particles 15-53 μm, and SiC particles 0.1-5 μm. The purity of the Ti particles is ≥ 99.99%, and the purity of both the TC4 and SiC particles is ≥ 90%.

[0035] Ti particles (0.1-25 μm in size, purity ≥99.99%) belong to the submicron to micron-scale metallic reinforcing phase. TC4 particles (15-53 μm in size, purity ≥90%) belong to the micron-scale metallic reinforcing phase. Both TC4 and Ti particles are titanium-based materials, exhibiting good interfacial compatibility. Ti particles can act as an interfacial transition between TC4 particles and the magnesium matrix, mitigating the performance differences between TC4 and the matrix. SiC particles (0.1-5 μm in size, purity ≥90%) belong to the submicron to micron-scale ceramic reinforcing phase. The three particle types, through gradation at different scales, achieve complementary advantages between the micron-scale metallic phase and the submicron to micron-scale ceramic phase, avoiding the strengthening limitations of a single reinforcing phase.

[0036] Next, this invention achieves the preparation of the above-mentioned composite material through the following five core steps. It should be noted that there is a strict order between these steps, and they cannot be arbitrarily changed. The following is a detailed explanation of each step: S1. Melting and Casting: Weigh Mg, Gd, Y, Zn, and Mn raw materials according to the specified ratio, melt them in a vacuum, and add refining agents for refining treatment to obtain a homogeneous magnesium alloy melt. Based on the total mass of the target magnesium-based composite material, add Ti particles (particle size 0.1-25μm, purity ≥99.99%), TC4 particles (particle size 15-53μm, purity ≥90%), and SiC particles (particle size 0.1-5μm, purity ≥90%) according to the specified ratio. Stir thoroughly to ensure uniform dispersion of particles in the melt, and then cast into a composite ingot. Melting and casting is the initial step in preparing the composite material, and its purpose is to initially combine the magnesium matrix with the reinforcing phase. The vacuum environment can eliminate air in the furnace, reduce the source of oxidation during the melting process, and the refining treatment can remove gases and inclusions in the melt, ensuring the purity of the matrix. Adding reinforcing particles to the melt and stirring allows the particles to be initially dispersed in the matrix, laying the foundation for subsequent processing. This step must be completed before S2, because only after obtaining the composite ingot can the subsequent homogenization solution treatment be carried out. The quality of the casting directly affects the success or failure of all subsequent steps, and the initial distribution state of the reinforcing phase in the ingot directly affects the final uniformity of the distribution after subsequent deformation. S2. Two-stage homogenization solution treatment: The composite ingot is placed in a heating furnace and first held at 400-450℃ for 4 hours, then heated to 500℃ and held for 12 hours. After holding, it is first air-cooled for 5-15 minutes, then water-quenched to room temperature to obtain a solution-treated billet. Two-stage homogenization solution treatment is one of the key innovative steps of this invention. As-cast alloys inevitably contain compositional segregation and coarse non-equilibrium second phases. If these structural defects are carried into subsequent deformation processes, they will seriously affect the forming performance and final mechanical properties of the material. The first stage, a low-temperature treatment at 400-450℃ for 4 hours, homogenizes the internal temperature of the ingot and initially dissolves some of the low-melting-point eutectic phase. The second stage, a high-temperature treatment at 500℃ for 12 hours, allows rare earth elements such as Gd and Y to fully dissolve in the magnesium matrix, while simultaneously eliminating compositional segregation. Compared to conventional single-stage high-temperature, long-duration solution treatment, the two-stage process effectively avoids abnormal grain growth caused by excessively high temperatures and prolonged treatment times, maintaining a fine grain structure while ensuring sufficient solution dissolution. The segmented cooling method, involving air cooling for 5-15 minutes followed by water quenching, avoids excessive thermal stress leading to ingot cracking caused by direct water quenching, while ensuring a sufficient cooling rate to suppress the re-precipitation of the second phase. This step must be performed after S1 and before S3. If the cast ingot is directly subjected to extrusion deformation, the coarse as-cast structure and uneven composition distribution will result in uneven deformation, a high risk of cracking, and poor dispersion of the reinforcing phase. Only after sufficient solution treatment, with a uniform matrix composition and fine structure, can a uniform deformed structure and good reinforcing phase distribution be obtained during subsequent extrusion. S3, Two-stage gradient extrusion: The solution-treated billet is extruded and deformed using a two-stage extrusion scheme with varying temperature and extrusion ratio. The first stage extrusion temperature is 470-530℃, the extrusion ratio is 9, and the extrusion speed is ≤3mm / s; the second stage extrusion temperature is 370-430℃, the extrusion ratio is 7, and the extrusion speed is ≤3mm / s. After extrusion, an extruded profile is obtained. Two-stage gradient extrusion is one of the core technologies of this invention and is also the key to achieving uniform dispersion of the reinforcing phase and strengthening of the interface. The first stage is extruded at a high temperature (470-530℃) with a large extrusion ratio (9). The high temperature is conducive to the plastic flow of the matrix, and the large deformation generates strong triaxial compressive stress, which breaks up the agglomerated reinforcing particles in the ingot and initially disperses them in the matrix. At the same time, the high temperature and large deformation promote the dynamic recrystallization of the matrix and refine the grain structure. The second stage involves extrusion at a lower temperature (370-430℃) with an extrusion ratio of 7. The lower temperature increases the flow stress in the matrix, causing relative slippage and diffusion bonding at the interface between the reinforcing phase and the matrix under shear stress, thus forming a good metallurgical interface. The extrusion speed in both stages is controlled to ≤3mm / s to avoid adiabatic temperature rise and microstructure coarsening caused by high-speed extrusion. This step must be performed after S2 and before S4. The solution-treated billet has a uniform microstructure and good plasticity, suitable for large deformation extrusion. If extrusion is performed directly without solution treatment, the coarse phases in the as-cast microstructure will lead to stress concentration and cracking during extrusion. Extrusion must be completed before rolling because it shapes the billet into a profile suitable for rolling, and it imparts a specific deformation texture and microstructure to the material, providing suitable initial conditions for subsequent low-temperature rolling. The order of extrusion and rolling cannot be reversed. If rolling precedes extrusion, the rolled sheet cannot be extruded again, and the process route is invalid. S4. Low-Temperature Multi-Segment Rolling: The extruded profile is rolled in multiple passes at 150-250℃, with each pass reducing the material by 1-2%, and the total reduction controlled within 10%, to obtain the rolled material. Low-temperature multi-segment rolling is a key step in the fine control of microstructure in this invention. Rolling at a low temperature of 150-250℃ primarily results in dislocation slip and dynamic recovery in the matrix. Dislocations accumulate within the grains and form dislocation entanglements, controlling grain orientation and further refining the grains. Only a small reduction of 1-2% is applied per pass to avoid stress concentration and cracking caused by a large deformation at once, as magnesium alloys have poor plasticity at low temperatures, and large reductions easily lead to cracking. The total reduction accumulated over multiple passes does not exceed 10%, ensuring that the material does not fail while effectively controlling dislocation density and grain orientation. This step must be performed after S3 and before S5. Extruded profiles possess favorable deformation texture and refined grain structure, providing a suitable microstructure basis for low-temperature rolling. If cast materials are rolled directly without prior extrusion, the coarse structure and uneven distribution of reinforcing phases in the cast state result in poor deformation coordination, making it difficult to achieve the desired microstructure refinement and increasing the risk of cracking at low temperatures. Furthermore, the cross-sectional shape of extruded profiles is suitable for rolling, and the dislocation structure and grain refinement introduced by rolling deformation are prerequisites for the uniform precipitation of nanophases during subsequent aging treatment. The dislocations introduced by deformation provide more nucleation sites for aging precipitation, promoting a fine and dispersed distribution of the precipitated phases. If aging precedes rolling, the aging-precipitated nanophases will be destroyed or coarsened during the subsequent rolling deformation, failing to exert a strengthening effect. S5. Aging Heat Treatment: The rolled material is held at 150-250℃ for 3-4 hours, followed by air cooling to room temperature to obtain the final high-strength magnesium-based composite material. Aging heat treatment is a crucial step in obtaining the final ultra-high strength in this invention. Holding at 150-250℃ for 3-4 hours allows supersaturated solid solutions of rare earth elements such as Gd and Y in the matrix to precipitate uniformly in the form of nanoscale precipitates. These nanoscale precipitates are coherent or semi-coherent with the matrix, effectively hindering dislocation movement and producing a significant precipitation strengthening effect. The nanoscale precipitates, together with the aforementioned multi-scale reinforcing phases (Ti, TC4, SiC), form a multi-layered strengthening network of "nanoprecipitate-micron reinforcement," further enhancing the material's strength. The 3-4 hour holding time ensures sufficient aging precipitation, and air cooling avoids thermal stress caused by rapid cooling. This step must be placed after S4; it is the final step in the entire process. Aging treatment must be performed after all plastic deformation is completed, because once nanoscale precipitates form during the aging process, any subsequent hot deformation will cause the precipitates to be sheared, broken, or coarsened, thus losing their strengthening effect. Therefore, arranging all deformation processes (extrusion, rolling) before aging is a necessary condition to ensure the stable existence of the precipitates and their strengthening effect.

[0037] In summary, the five steps of this invention follow a strict sequential order: first, a composite material ingot is obtained through melting and casting; then, the microstructure is homogenized through solution treatment; next, the reinforcing phase is dispersed and the interface is strengthened through gradient extrusion; then, the microstructure is finely controlled through low-temperature rolling; and finally, the strength is significantly increased through aging heat treatment. The omission or simplification of any of these key steps will significantly reduce the material strength, making it difficult to consistently achieve a strength above 550 MPa.

[0038] Example 1

[0039] This embodiment provides a high-strength magnesium-based composite material and its preparation method, with the specific steps as follows: S1. Melting and Casting: Weigh the raw materials according to the following mass percentages: Gd 12.6%, Y 1.3%, Zn 0.9%, Mn 0.5%, with the balance being Mg and unavoidable impurities. Melt the materials in a vacuum and add a refining agent to obtain a magnesium alloy melt. Based on the total mass of the target magnesium-based composite material, add 1.2% Ti particles (particle size 0.1-25μm, purity ≥99.99%), 4% TC4 particles (particle size 15-53μm, purity ≥90%), and 0.9% SiC particles (particle size 0.1-5μm, purity ≥90%). After thorough mixing, cast the mixture into a composite ingot. S2, Two-stage homogenization solution treatment: The composite ingot is kept at 400℃ for 4 hours, then heated to 500℃ and kept at 500℃ for 12 hours, air-cooled for 10 minutes and then water-quenched to room temperature to obtain a solution-treated billet. S3, Two-stage gradient extrusion: The solution-treated billet is extruded and deformed. The first stage extrusion temperature is 500℃, the extrusion ratio is 9, and the extrusion speed is 3mm / s; the second stage extrusion temperature is 400℃, the extrusion ratio is 7, and the extrusion speed is 0.1mm / s, to obtain the extruded profile. S4. Low-temperature multi-stage rolling: The extruded profile is rolled in multiple passes at 200℃, with a reduction of 1% in each pass and a total reduction of 6% to obtain the rolled material. S5. Aging heat treatment: The rolled material is kept at 200℃ for 3 hours and then air-cooled to room temperature to obtain the final high-strength magnesium-based composite material.

[0040] Comparative Example 1 The only difference between this comparative example and Example 1 is that Ti particles, TC4 particles, and SiC particles are not added in step S1, thus obtaining a Mg-Gd-Y-Zn-Mn alloy without reinforcing phases. The remaining steps are exactly the same as in Example 1.

[0041] Comparative Example 2 The only difference between this comparative example and Example 1 is that the two-stage gradient extrusion in step S3 is changed to a single-stage extrusion, that is, the first stage extrusion is omitted, and only the second stage extrusion is performed. The remaining steps are exactly the same as in Example 1.

[0042] Comparative Example 3 The only difference between this comparative example and Example 1 is that steps S4 (low-temperature multi-stage rolling) and S5 (aging heat treatment) are omitted, meaning the final material is obtained directly after extrusion. The remaining steps are exactly the same as in Example 1.

[0043] Comparative Example 4 The only difference between this comparative example and Example 1 is that step S5 (aging heat treatment) is omitted, meaning the final material is obtained directly after rolling. The remaining steps are exactly the same as in Example 1.

[0044] The materials obtained in Example 1 and Comparative Examples 1-4 were subjected to room temperature tensile property tests. The test results were then analyzed.

[0045] The test method is as follows: A universal testing machine was used for room temperature tensile testing at a tensile rate of 1 mm / min. At least three parallel specimens were tested for each example and comparative example, and the average value was taken. Tensile strength, yield strength, and elongation after fracture were determined according to GB / T 228.1-2021 "Metallic materials, tensile testing—Part 1: Test at room temperature".

[0046] The room temperature tensile curves for each embodiment and comparative example are shown below. Figure 1-5 The test results are shown in Table 1.

[0047] Table 1. Room temperature tensile properties of each embodiment and comparative example

[0048] As shown in Table 1: (1) Comparing Example 1 and Comparative Example 1, Comparative Example 1 did not add any reinforcing phase, and the rest of the process was exactly the same as Example 1. Its tensile strength was 536 MPa, yield strength was 511 MPa, and elongation was 1.85%. After adding 1.2% Ti + 4% TC4 + 0.9% SiC ternary reinforcing phase, the tensile strength of Example 1 increased significantly to 592 MPa, but the yield strength decreased to 489 MPa and the elongation increased to 2.46%. It is worth noting that during the research and development process, it was unexpectedly discovered that after the above-mentioned full-process treatment, the yield strength did not increase in sync with the tensile strength as expected, but instead showed a moderate decrease. This is likely because the two-stage gradient extrusion and low-temperature multi-stage rolling introduce a bimodal fine-grained structure and a large number of mobile dislocations into the matrix, significantly lowering the threshold for basal slip initiation (the microscopic root cause of yield strength reduction). Meanwhile, the ternary multi-scale reinforcing phase and the subsequent aging-precipitated nanoscale precipitates exert a strong pinning and storage effect on dislocations during the subsequent plastic deformation stage, providing extremely high subsequent strain hardening capability and significantly increasing the tensile strength to 592 MPa. Although "yield reduction" was not the original design endpoint of this invention, this phenomenon precisely endows the material with the advantageous deformation characteristics of "low yield combined with high work hardening," enabling the material to initiate plastic deformation under relatively low stress, effectively suppressing premature necking. Ultimately, while achieving an ultra-high tensile strength exceeding 550 MPa, it also unexpectedly improved plasticity matching, further verifying the uniqueness and superiority of the entire process path of this invention. (2) A comparison between Example 1 and Comparative Example 2 shows that Comparative Example 2 changed the two-stage gradient extrusion to a single-stage extrusion (only the second stage was retained: 400℃, extrusion ratio 7, speed 0.1mm / s), while the rest of the process was exactly the same as in Example 1. The tensile strength of Comparative Example 2 was only 296MPa, the yield strength was only 228MPa, and the elongation was as high as 8.07%. The single-stage extrusion lacked the breaking and dispersing effect of the first stage's high-temperature large deformation on the reinforcing phase agglomerates, resulting in severe agglomeration of Ti, TC4, and SiC particles, which failed to form an effective multi-scale gradation distribution, bimodal fine-grained structure, and movable dislocation structure in the matrix. The agglomerated reinforcing phase not only failed to play a role in bearing and synergistic hardening, but also became a stress concentration source for crack initiation, causing the material to fail at a low stress and its strength to drop significantly. The matrix itself, because it had not undergone sufficient deformation strengthening, retained good plastic deformation capacity and therefore exhibited high elongation. (3) As can be seen from Example 1 and Comparative Example 3, Comparative Example 3 eliminated the low-temperature multi-stage rolling and aging heat treatment, that is, the final material was obtained directly after two-stage gradient extrusion. The tensile strength of Comparative Example 3 was 531 MPa, the yield strength was 518 MPa, and the elongation was 2.37%.The lack of low-temperature multi-stage rolling means that a large number of mobile dislocations and bimodal fine-grained structures cannot be introduced into the matrix, and the basal slip initiation threshold is not effectively reduced, so the yield strength is as high as 518 MPa; at the same time, the lack of aging heat treatment means that nanoscale strengthening phases cannot be precipitated in the matrix. The absence of both results in the basal slip initiation threshold not being effectively reduced, and the tensile strength is only 531 MPa. Since the difference between yield strength and tensile strength is small (low work hardening rate), the material quickly enters the necking stage after reaching yield, and the plasticity is not effectively improved. (4) As can be seen from Example 1 and Comparative Example 4, Comparative Example 4 only cancels the aging heat treatment and retains all other processes, including low-temperature multi-stage rolling. The tensile strength of Comparative Example 4 is 542 MPa, the yield strength is 526 MPa, and the elongation is 1.53%. Although low-temperature rolling introduces dislocations, the lack of age-precipitated nanophases to form favorable interactions with them makes it difficult for these dislocations to be activated during the initial stretching phase. The basal slip initiation threshold is not effectively lowered, and the yield strength remains at a relatively high level of 526 MPa. Simultaneously, the lack of nanoprecipitated phases results in insufficient dislocation inhibition during deformation, limiting subsequent strain hardening capacity, and a tensile strength of only 542 MPa. The high yield strength and limited work hardening capacity cause the material to rapidly neck after yielding, with elongation dropping to 1.53% and significant deterioration in plasticity.

[0049] Based on the above analysis, the following conclusions can be drawn: (1) By introducing the Ti+TC4+SiC ternary multi-scale reinforcing phase, combined with the process route of two-stage gradient extrusion, low-temperature multi-stage rolling and aging heat treatment, the present invention has achieved the technical goal of tensile strength exceeding 550MPa; (2) Two-stage gradient extrusion is the core process for achieving uniform dispersion of the reinforcing phase. Single-stage extrusion cannot effectively disperse the reinforcing phase, resulting in a significant decrease in strength; (3) Low-temperature multi-stage rolling and aging heat treatment are necessary steps to obtain the performance indicators of the present invention. Comparative Example 3 lacks both steps, and Comparative Example 4 lacks only aging. The tensile strength of both failed to reach 550 MPa, indicating that both steps are indispensable. (4) The five steps of this invention (melting and casting → solution treatment → extrusion → rolling → aging) constitute a complete process chain. The absence or simplification of any link will prevent the acquisition of high-performance magnesium-based composite materials with tensile strength exceeding 550MPa.

[0050] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the invention in any way. All equivalent transformations or modifications made in accordance with the essence of the present invention should be covered within the protection scope of the present invention.

Claims

1. A high-strength magnesium-based composite material, characterized in that, It consists of a magnesium matrix and a multi-scale composite reinforcing phase uniformly dispersed within the magnesium matrix; The magnesium matrix is ​​a Mg-Gd-Y-Zn-Mn series magnesium alloy, which contains the following components by mass percentage: Gd 12.6%, Y 1.3%, Zn 0.9%, Mn 0.5%, with the balance being Mg and unavoidable impurities; The multi-scale composite reinforcing phase is composed of Ti particles, TC4 particles, and SiC particles. Based on the total mass of the magnesium matrix composite, the mass fractions of Ti particles, TC4 particles, and SiC particles are Ti≤4%, TC4≤7%, and SiC≤2%, respectively. Furthermore, the Ti particles, TC4 particles, and SiC particles exhibit a multi-scale gradation distribution in the magnesium matrix, wherein the particle size of Ti particles is 0.1-25 μm, the particle size of TC4 particles is 15-53 μm, and the particle size of SiC particles is 0.1-5 μm.

2. The high-strength magnesium-based composite material according to claim 1, characterized in that, Ti particles have a purity of ≥99.99%, while TC4 and SiC particles both have a purity of ≥90%.

3. The high-strength magnesium-based composite material according to claim 1, characterized in that, Based on the total mass of the magnesium-based composite material, the mass fractions of Ti particles, TC4 particles and SiC particles were 1.2%, 4% and 0.9%, respectively.

4. The high-strength magnesium-based composite material according to claim 1, characterized in that, The resulting magnesium-based composite material has a room temperature tensile strength of 550-600 MPa, a yield strength of 480-520 MPa, and an elongation of 2.0-3.0%.

5. A method for preparing a high-strength magnesium-based composite material as described in any one of claims 1-4, characterized in that, include: S1. Melting and casting: Weigh Mg, Gd, Y, Zn and Mn raw materials according to the proportion, melt and refine them in vacuum, add the corresponding amount of Ti particles, TC4 particles and SiC particles based on the total mass of the target magnesium-based composite material, mix them evenly and cast them into a composite ingot. S2, Two-stage homogenization solution treatment: The composite ingot is kept at 400-450℃ for 4 hours, then at 500℃ for 12 hours, air-cooled for 5-15 minutes, and then water-quenched to room temperature to obtain a solution-treated billet. S3. Two-stage gradient extrusion: The solution-treated billet is subjected to a first stage extrusion and a second stage extrusion in sequence. The first stage extrusion temperature is 470-530℃, the extrusion ratio is 9, and the speed is ≤3mm / s; the second stage extrusion temperature is 370-430℃, the extrusion ratio is 7, and the speed is ≤3mm / s, to obtain an extruded profile. S4. Low-temperature multi-stage rolling: The extruded profile is rolled in multiple passes at 150-250℃, with a reduction of 1-2% per pass and a total reduction of ≤10%, to obtain the rolled material. S5. Aging heat treatment: The rolled material is held at 150-250℃ for 3-4 hours and then air-cooled to obtain the high-strength magnesium-based composite material.

6. The preparation method according to claim 5, characterized in that, In step S2, the air cooling time is 10 minutes.

7. The preparation method according to claim 5, characterized in that, In step S3, the first extrusion temperature is 500℃ and the speed is 3mm / s, and the second extrusion temperature is 400℃ and the speed is 0.1mm / s.

8. The preparation method according to claim 5, characterized in that, In step S4, the rolling temperature is 200℃, the total reduction is 6%, and the reduction per pass is 1%.

9. The preparation method according to claim 5, characterized in that, In step S5, the aging temperature is 200℃ and the holding time is 3h.

10. The preparation method according to claim 5, characterized in that, In step S1, the added Ti particles have a particle size of 0.1-25 μm and a purity of ≥99.99%. TC4 particles have a diameter of 15-53 μm and a purity of ≥90%; The SiC particles have a particle size of 0.1-5μm and a purity of ≥90%.